Budidaya Pakis Sayur (Diplazium Esculentum) dan Pembibitan Tanaman Karet (Hevea Brasiliensis) di Desa Ciwalen - Ibrahim Danuwikarsa (LPPM UNINUS, 2015)
To reduce the encroachment by the people living around the forest, Perum Perhutani has initiated a program called Forest Management with Community System. The community around the forest at Ciwalenvillage, sub Dayeuh Luhur, Cilacap district, Central Java province, has establishedForest Village Community Organization of Galih Rimba. The Writers implementedThe Community Service Program with Forest Village Community Organization of Galih Rimba,in form of: (1) Training and Pilottingthe cultivationof fern (Diplazium esculentum) in the area of pine forest at Perum Perhutani KPH West Banyumas plots 26A and on land owned by the community. (2) Training and Pilottingthe cultivation of rubber (Hevea Brasiliensis) to supply the needs of qualified rubber to assist farmers at Forest Village Community Organization of Galih Rimba and the farming community in general. From the program implementation and discussion, it results: (1) The program can be implemented through the active participation of its officials working partners,Forest Village Community Organization of Galih Rimba. (2) The knowledge and practical skills improvement of program participants have been there, yet it has not reached an economic value. (3) It is necessary to hold scheduled further programs for achieving the targeted farmers as participants at Forest Village Community Organization of Galih Rimba gradually and produce valuable and economical products.